2020
DOI: 10.1177/1744806920929246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of reactive oxygen species of the psoas major muscle in complete Freund’s adjuvant-induced inflammatory pain in rats

Abstract: Lower limb pain is a common clinical disease that affects millions of people worldwide. It is found in previous studies that reactive oxygen species is closely related to neuropathic, cancer, chemotherapy, and inflammatory pain, which can be relieved by reactive oxygen species scavengers. Furthermore, acupuncture or electroacupuncture on the psoas major muscle has a great effect on adjuvant-induced arthritis and lower back pain. In our study, we investigated the function of reactive oxygen species scavengers l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 44 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…ROS and lipid peroxidation products as a result of oxidative stress contribute to chronic pain via multiple mechanisms, including direct activation of nociceptor TRPA1 in the periphery and activation of microglia in the spinal cord, affecting spinal synaptic plasticity or producing pain-inducing substances [32,[58][59][60]. ROS scavengers or NADPH oxidase inhibitors, which reduce oxidative stress and ROS production, ameliorate chronic pain [61][62][63][64]. The Nrf2 antioxidant signaling is an endogenous machinery to counteract oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…ROS and lipid peroxidation products as a result of oxidative stress contribute to chronic pain via multiple mechanisms, including direct activation of nociceptor TRPA1 in the periphery and activation of microglia in the spinal cord, affecting spinal synaptic plasticity or producing pain-inducing substances [32,[58][59][60]. ROS scavengers or NADPH oxidase inhibitors, which reduce oxidative stress and ROS production, ameliorate chronic pain [61][62][63][64]. The Nrf2 antioxidant signaling is an endogenous machinery to counteract oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“… 28 Findings from our previous study showed that local injection of the ROS scavenger N-tert-Butyl-a-phenylnitrone (PBN) to psoas major muscle significantly ameliorated pain and swelling in the hind paws of inflamed rats. 13 These findings indicate that local injection of α 2 adrenergic receptor agonists into the psoas major muscle of rats may result in analgesic and anti-inflammatory effects. In the present study, low-dose α 2 adrenergic agonists, dexmedetomidine and clonidine, were administered into the psoas major muscle of CFA-induced inflammatory rats to explore the local analgesic effect and mechanism of α 2 adrenergic agonists.…”
Section: Introductionmentioning
confidence: 87%
“…Inflammatory model was established as described previously. 13 Rats were anesthetized and were subjected to 3% sevoflurane by inhalation to maintain mild anesthesia. The skin of the left foot base was disinfected using 75% medical alcohol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations